The Neurobiology of Love and Pair Bonding from Human and Animal Perspectives - Sarah A. Blumenthal; Larry J. Young (Biology, 2023)
Love is a powerful emotional experience that is rooted in ancient neurobiological processes shared with other species that pair bond. Considerable insights have been gained into the neural mechanisms driving the evolutionary antecedents of love by studies in animal models of pair bonding, particularly in monogamous species such as prairie voles (Microtus ochrogaster). Here, we provide an overview of the roles of oxytocin, dopamine, and vasopressin in regulating neural circuits responsible for generating bonds in animals and humans alike. We begin with the evolutionary origins of bonding in mother–infant relationships and then examine the neurobiological underpinnings of each stage of bonding. Oxytocin and dopamine interact to link the neural representation of partner stimuli with the social reward of courtship and mating to create a nurturing bond between individuals. Vasopressin facilitates mate-guarding behaviors, potentially related to the human experience of jealousy. We further discuss the psychological and physiological stress following partner separation and their adaptive function, as well as evidence of the positive health outcomes associated with being pair-bonded based on both animal and human studies.